Digital Interventions for Social Participation in Adults with Long-term Physical Conditions: A Systematic Review - Deng, Huan; Vu, Kevin Q.; Franco, Jessie R.; Shepler, Lauren J.; Abouzeid, Cailin A.; Hamner, J. W.; Mercier, Hannah W.; Taylor, J. Andrew; Kazis, Lewis E.; Slavin, Mary D.; Ryan, Colleen M.; Schneider, Jeffrey C. (Journal of medical systems, 2023)
This review aims to identify and evaluate digital interventions for social participation in the growing population of adults with long-term physical conditions. Articles were sourced from MEDLINE, EMBASE, CINAHL and PsycINFO databases using subject headings and keywords related to “social participation” and “digital technology”. Studies that adopted digital technology interventions to improve social participation in adults with long-term physical conditions were included. Data on study methodology, participant and digital intervention characteristics, and findings related to social participation were extracted. The search yielded a total of 4646 articles and 14 articles met criteria for final review with five randomized controlled trials, two non-randomized clinical trials and seven one-group pretest–posttest clinical trials. Studies were organized based on the digital intervention strategy implemented to improve social participation: group support ( n = 4), individual skill training or counseling ( n = 6), education and support ( n = 3), and mixed intervention ( n = 1). The group support interventions developed a social network among participants through videoconference, app, or virtual reality platform. Three studies reported positive improvements in different aspects of social participation. Individual skill training or counseling mainly utilized phone calls to help participants cope with activity participation and interpersonal relationship issues. Only two studies demonstrated benefits for social participation. The education and support intervention, which used messages and website information to increase participants’ knowledge and provide support, showed positive findings in three studies. This review suggests digital interventions for improving social participation in adults with long-term physical conditions are feasible and the effectiveness of different strategies may vary. Registration: This review was prospectively registered on the International Prospective Register of Systematic Reviews (PROSPERO) (registry number: CRD42021254105).